Primary myxoid and epithelioid mesenchymal tumor of the kidney with a novel GLI1‐FOXO4 fusion. Issue 2 (18th November 2020) - Pettus, Jason R.; Kerr, Darcy A.; Stan, Radu V.; Tse, Julie Y.; Sverrisson, Einar F.; Bridge, Julia A.; Linos, Konstantinos
Abstract: To our knowledge, we describe the first mesenchymal tumor with a novel GLI1‐FOXO4 fusion gene. This well‐circumscribed kidney tumor displayed variably myxoid and epithelioid histologic features with a focally nodular growth pattern. The tumor cells showed bland, round to ovoid nuclei, with no overt high‐grade features. The tumor showed focal immunopositivity for smooth muscle actin and Melan‐A, which raised the possibility of a relationship with a perivascular epithelioid cell tumor. The clinical and morphologic features appear distinct from other reported neoplasms harboring GLI1 or FOXO4 gene rearrangements. The patient underwent radical nephrectomy and is without evidence of disease during a relatively short clinical follow‐up period. However, the features of this tumor likely warrant long‐term follow‐up to monitor for the possibility of a late recurrence or metastasis. In addition to reporting this novel fusion‐positive tumor, we also provide a brief review of GLI1 and FOXO4 gene functions in both normal and neoplastic contexts.